Безперервний професійний розвиток лікарів-педіатрів – досвід роботи кафедри - Подліанова, Олена Іванівна; Podlianova, E. I.; Подлианова, Е. И. (ВДНЗ «Українська медична стоматологічна академія», 2014)
У статті розглядається досвід організації безперервного професійного розвитку лікарів-слухачів педіатрів на кафедрі дитячих хвороб ФПО ЗДМУ на прикладі курсів тематичного удосконалення лікарів-педіатрів. Наш досвід роботи із лікарями-слухачами курсів ТУ свідчить про наступне: викладання на післядипломному етапі лікарям-слухачам курсів тематичного удосконалення з педіатрії доцільно комбінувати, поєднуючи очний та дистанційний методи навчання; згідно результатів анкетування, дистанційне навчання з використанням сучасних комп’ютерних технологій сприймають позитивно 100 % лікарів-слухачів; вагомою перевагою комбінованого методу навчання є можливість економії коштів (витрати на відрядження слухача, оплата сумісництва) лікувальним закладом. This article reviews the experience of continuous professional development of medical students-pediatricians at FPE ZSMU Department of children illnesses on the example of the thematic improvement courses for pediatricians. The European Union of Medical Specialists gives the definition of continuous professional development (CPD) as an educational method of improving, updating and restoring of doctors’ professional knowledge. The necessity of CPD system for Ukraine is due to many factors. The implementation of CPD programs is conducted under the orders and instructions of the Ministry of Health of Ukraine. However, we need a strong feedback of state structures and departments of universities which seek for modern, adapted to our society forms of CPD. This experience should be used to create national strategies of CPD. The aim of research. To analyze the work of the department of children illnesses, Faculty of Postgraduate Education (FPE) ZSMU, with the doctors who participate in the courses concerning the objectives of CPD. The results and their discussion. The implementation of competence-based approach to pediatricians’ training at the courses of thematic improvement at the Department provides a broad use of active and interactive forms in educational process. During the courses, the combined method of education, which consists of classroom and extracurricular work carried out in full-time and part-time departments, is used. The students, within the existing program, choose the topics of the course. During the classroom work we use various forms of training: lectures and discussions, business games; studying of patients’ cases, master-classes on emergency pre-medical and medical care using the special simulator classroom. Within each course 2 or 3 round tables are conducted with the participation of different specialists (TB specialists, immunologists, doctors of AIDS medical center, transfuziologists). Extracurricular work includes the course participants’ practice at the workplace and the use of modern computer technologies for distance education, including using the platform Moodle. The control of knowledge and skills of students is held twice – at the beginning and at the end of the course. The Department’s good tradition is to conduct an anonymous questionnaire at the end of the courses. After each course the Department holds meetings where teachers analyze students’ questionnaires, discuss the organization of the educational process, correct further strategies of the Department regarding CPD doctors- pediatricians, students of the courses. Conclusions: the teaching at postgraduate stage of doctors -students of the courses of thematic improvement in Pediatrics is advisable to combine the full-time and the distance methods of education; according to the questionnaire results, distance education using modern computer technology is perceived positively by 100 % doctors- students of the courses; a significant advantage of the combined method of education is the possibility of saving money (travel expenses for a student, salary for a person who works instead of the student of the courses) by medical institution. В статье рассматривается опыт организации беспрерывного профессионального развития врачей-слушателей педиатров на кафедре детских болезней ФПО ЗДМУ на примере курсов тематического усовершенствования врачей-педиатров. Наш опыт работы с врачами-слушателями курсов ТУ свидетельствует о следующем: преподавание на последипломном этапе врачам-слушателям курсов тематического усовершенствования из педиатрии целесообразно комбинировать, сочетая стационарный и дистанционный методы учебы; согласно результатов анкетирования, дистанционную учебу с использованием современных компьютерных технологий воспринимают положительно 100 % врачей-слушателей; весомым преимуществом комбинированного метода учебы является возможность экономии средств (командировочные расходы слушателя, оплата совместительства) лечебным заведением.
Беспрерывное профессиональное развитие врачей-педиатров - опыт работы кафедры
Continuous professional development of pediatricians - the experience of the department
Keywords: безперервна професійна освіта; лікарі-слухачі педіатри; беспрерывное профессиональное развитие; врачи-слушатели педиатры; continuous professional development; medical students-pediatricians